Seed provision and dryland crops in the semiarid regions of Eastern Kenya - Nagarajan, Latha; Audi, Patrick; Jones, Richard; Smale, Melinda (International Food Policy Research Institute, 2007)
Over the last two decades, several seed-related programs have been initiated in eastern Kenya to improve farmers’ access to quality seeds of dryland cereals and legumes. They are provided during two occasions, regular and emergency times. But very often, the formal supply mechanisms limit their role in provision of seeds other than maize. In the absence of any formalized systems of seed provision for other dryland crops, such as sorghum and pigeon pea, farmers have preferred local markets for their seed needs, especially during distress periods. Here we have examined the role of various seed-intervention programs in eastern Kenya, along with the strengths and weaknesses of each program. We have also underscored the importance of local markets and their actors in meeting the needs for non-maize and bean seeds in these marginal environments. For this purpose, detailed, informal interviews were conducted during October–December 2005 with all the stakeholders, namely public and private institutions and vendors in eight major local markets in eastern Kenya. The results of the study call for synergies between existing formal (private, public, and other development initiative) systems and informal (local market) seed systems to enhance crop yields and the diversity of dryland cereals and legumes through effective seed-supply interventions.